Analisis Pembelajaran Psikologi Pendidikan - Uliyanda, Dewi; Syabrina, Laila; Khairani, Shofi ,; Az-Zahra, Maysa; Dalimunthe, Putri Ani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education psychology can also be seen as a science that is easy to understand, which explains learning in accordance with the rules in educational psychology that have been scientifically determined based on the factcs of human behavior. Psychology is an implementation of principles and methods in educational psychology which are useful for helping the application of science to student by paying attention to the principles of physicial development in students. Educational psychology also includes change which is expressed as a process that includes all forms of activities in the teaching and learning process that are beneficial to individuals and groups in the social environment so that it can help to develop behavior and habits or social norms from one generation to the next generation will come.